2022
DOI: 10.1039/d2ra03007a
|View full text |Cite
|
Sign up to set email alerts
|

Fly ash derived calcium silicate hydrate as a highly efficient and fast adsorbent for Cu(ii) ions: role of copolymer functionalization

Abstract: Acumer2000 modified calcium silicate hydrate was prepared using fly ash, and displayed outstanding adsorption performance for Cu(ii) no matter whether in powder or film state through inhibiting the formation of by-products and enhancing surface complexation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Hussain et al [ 51 ] found that the alkaline character of the CFA neutralizes the metal solution, which is linked to the removal efficiency. Notably, CFA is able to adsorb trace metals without being impacted by high ionic strength or notable amounts of Cl and Ca [ 67 ]. When the concentration of calcium (CaO) increases, CFA adsorption efficiency increases as well [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hussain et al [ 51 ] found that the alkaline character of the CFA neutralizes the metal solution, which is linked to the removal efficiency. Notably, CFA is able to adsorb trace metals without being impacted by high ionic strength or notable amounts of Cl and Ca [ 67 ]. When the concentration of calcium (CaO) increases, CFA adsorption efficiency increases as well [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study showed that up to 90–95 % of Cu and Zn are removed by the generated adsorbent in batch and column studies. When the adsorption of both metal ions increased with temperature, it was demonstrated that the adsorption process was exothermic [ 67 ]. The removal efficiency of metals is influenced by the concentration of the metals present in wastewater.…”
Section: Introductionmentioning
confidence: 99%